2001
DOI: 10.1046/j.1365-2613.2001.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyaluronan on the invasive properties of human breast cancer cells in vitro

Abstract: Hyaluronan (HA) is a high molecular weight glycosaminoglycan present mostly in the extracellular matrix (ECM). HA binds to specific receptors such as CD44. Its production is increased at the tumour-stroma interface, including those in breast cancer tumours. It has been suggested that it facilitates invasion of tumour cells into the ECM by a hydrodynamic effect, or by altering tumour cell behaviour. Using in vitro tests we studied the effect of immobilized (iHA) and soluble (sHA) HA on the invasive properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…The observed uptake of NS(HA) could be a result of non‐specific binding to the cells. Non‐specific binding may have resulted from the cell‐adhesion promoting property of HA, which has been implicated in cancer cell adhesion 21,22. When the cells were incubated with NS(HA)‐HER, a greater than seven‐fold increase in iron uptake [as compared to that for NS(HA)] was observed (59.5 ± 1.0 pg · cell −1 at 2 h and 197.5 ± 17.0 pg · cell −1 at 24 h).…”
Section: Resultsmentioning
confidence: 99%
“…The observed uptake of NS(HA) could be a result of non‐specific binding to the cells. Non‐specific binding may have resulted from the cell‐adhesion promoting property of HA, which has been implicated in cancer cell adhesion 21,22. When the cells were incubated with NS(HA)‐HER, a greater than seven‐fold increase in iron uptake [as compared to that for NS(HA)] was observed (59.5 ± 1.0 pg · cell −1 at 2 h and 197.5 ± 17.0 pg · cell −1 at 24 h).…”
Section: Resultsmentioning
confidence: 99%
“…Although mice lacking CD44 developed a similar incidence of primary tumors in response to the APC or p53 gene mutations as the CD44 expressing mice, knocking out CD44 resulted in a complete inability of these mice to develop metastatic lesions (Weber et al, 2002). In vitro studies have also demonstrated that HA promotes the invasion of breast cancer cells through experimental extracellular matrices as a consequence of activating CD44 (Herrera-Gayol and Jothy, 2001). Our laboratory has also recently established a role for CD44 expression in breast and prostate cancer cells in promoting their preferential adhesion to bone marrow endothelial cells (Draffin et al, 2004).…”
Section: Introductionmentioning
confidence: 87%
“…The capacity of these HA–L adducts in targeting CD44 receptors was explored with three tumor cell types (C6 rat glioma, B16‐F10 mice melanoma, and MCF7 human breast cancer) that have varied CD44 receptor expression levels 16. 22, 23 Cells (∼1.5×10 6 ) were incubated in medium containing HA–L (HA/liposome=4:1, the ratio of which is defined by moles of negative/positive charge), or nonfunctionalized Gd‐loaded liposomes (L) for 30 min. In both experiments the Gd concentration in the incubation medium was 0.01 m M .…”
Section: Methodsmentioning
confidence: 99%